SDN‐based architecture for providing quality of service to high‐performance distributed applications. Issue 5 (21st June 2019) - Oliveira, Alexandre T.; Martins, Bruno José C. A.; Moreno, Marcelo F.; Gomes, Antônio Tadeu A.; Ziviani, Artur; Borges Vieira, Alex
Summary: The specification of quality of service (QoS) requirements in most of the existing networks is still challenging. In part, traditional network environments are limited by their high administrative cost, although software‐defined networks (SDNs), a newer network paradigm, simplify the management of the whole network infrastructure. In fact, SDN provides a simple way to effectively develop QoS provisioning mechanisms. In this sense, we explore the SDN model and its flexibility to develop a QoS provisioning architecture. Through the use of our new architecture, network operators are able to specify QoS levels in a simple way. Each individual data flow can be addressed, and the architecture we propose also negotiates the QoS requirements between the network controller and applications. On the other hand, the network controller continuously monitors the network environment. Then, it allocates network elements resources and prioritizes traffic, adjusting the network performance. We evaluate the feasibility of our QoS provisioning mechanism by presenting three experimental setups under realistic scenarios. For example, for a given scenario where we evaluate file transfers, our results indicate that the additional SDN modules present negligible overhead. Moreover, for a given setup, we observe a reduction of up to 82% in the file transfer times. Abstract : Software‐defined networks (SDNs) simplify the management of network infrastructure and provides a simple way to effectively develop quality of service (QoS) provisioning mechanisms. In this article, we explore the SDN model and its flexibility to develop a QoS provisioning architecture. The architecture we propose negotiates the QoS requirements, at a flow granularity, between the network controller and applications and continuously monitors the network environment, adjusting the network performance to guarantee the QoS accordingly.